2021
DOI: 10.1007/s11071-020-06067-7
|View full text |Cite
|
Sign up to set email alerts
|

Stability and control of radial deployment of electric solar wind sail

Abstract: The paper studies the stability and control of radial deployment of an electric solar wind sail with the consideration of high-order modes of elastic tethers. The electric solar wind sail is modeled by combining the flexible tether dynamics, the rigid-body dynamics of central spacecraft, and the flexible-rigid kinematic coupling. The tether deployment process is modeled by the nodal position finite element method in the arbitrary Lagrangian-Eulerian framework. A symplectic-type implicit Runge-Kutta integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…A first step in this sense is represented by the recent work of Li et al [36], who included the tether flexility in the dynamical model as well as their kinematic coupling with the spacecraft rigid hub. The authors concentrated on a radial deployment strategy, and suggested using a proportional-derivative control law to achieve a given spin rate of the spacecraft body.…”
Section: Deployment Mechanismsmentioning
confidence: 99%
“…A first step in this sense is represented by the recent work of Li et al [36], who included the tether flexility in the dynamical model as well as their kinematic coupling with the spacecraft rigid hub. The authors concentrated on a radial deployment strategy, and suggested using a proportional-derivative control law to achieve a given spin rate of the spacecraft body.…”
Section: Deployment Mechanismsmentioning
confidence: 99%